2021
DOI: 10.1001/jamanetworkopen.2021.21443
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Regional Variation in Prevalence of Cardiovascular Risk Factors and Association With Socioeconomic Status in Canada, 2005-2016

Abstract: IMPORTANCECardiovascular disease remains the second leading cause of death in Canada. Monitoring and tracking the trends and disparities in major cardiovascular risk factors could provide benchmarks for future cardiovascular health strategies. OBJECTIVE To investigate the temporal trends, regional variations, and socioeconomic disparities in major cardiovascular risk factors in Canada from 2005 to 2016. DESIGN, SETTING, AND PARTICIPANTS This repeated cross-sectional survey study included adults aged 20 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Among our sample of primary care patients in Canada, 36% were considered to be in a high-risk group, which included a higher proportion of males, older adults, and individuals with lower SES. Our finding that patients who lived in areas associated with high levels of deprivation had an increasingly high-risk CVD profile is not surprising and is consistent with studies in Canada and other international jurisdictions [ 5 , 18 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among our sample of primary care patients in Canada, 36% were considered to be in a high-risk group, which included a higher proportion of males, older adults, and individuals with lower SES. Our finding that patients who lived in areas associated with high levels of deprivation had an increasingly high-risk CVD profile is not surprising and is consistent with studies in Canada and other international jurisdictions [ 5 , 18 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…[31][32][33][34][35] Our data suggest this is true for the Canadian PSOLAR population is consistent with this, as numerically higher rates of CVD were observed compared to the general population. 36 In addition, Papp et al (2010) investigated the epidemiologic features of patients with moderate to severe psoriasis in Canada and reported hypertension, dyslipidemia, and overweight/obesity as common comorbidities among the patients surveyed. 11 Similarly, in our analysis, hypertension (34.6%) and hyperlipidemia (24.3%) were found to represent the most prevalent cardiovascular risk factors among Canadian PSOLAR patients.…”
Section: Discussionmentioning
confidence: 99%
“…The link between hospital readmission and geographical factors is well-documented and unsurprising, given that regional health systems are independently operated and vary by spending, access, and health care service delivery. 26,27 With respect to the impact of discharge during Wave 3 of the COVID-19 pandemic, supplementary analyses found that hospital length of stay and service intensity following resumption of services did not significantly differ. Factors beyond the scope of this analysis that may help explain this effect include the fluctuating supply and demand for home care services, 17,28 emerging COVID-19 variants, 29 and subsequent public health and health system restrictions.…”
Section: Discussionmentioning
confidence: 99%